Short-term Impact of Anterior Cruciate Ligament Reconstruction in an Adolescent Population on 3D Knee Kinematics. Issue 7 (21st July 2017) - Laforest, Guillaume; Fuentes, Alexandre; Therrien, Marc; Grimard, Guy
Objectives: Gait analysis is a proven method for assessing knee biomechanical adaptations in anterior cruciate ligament deficient (ACLD) patients and to quantify the impact of the reconstructive surgery (ACLR). In an adult population, ACLR has shown partial kinematic correction, as they remain in internal tibial rotation, putting them at risk of rotational instability and develop osteoartitis. ACLD adolescents likely adopt similar gait changes to reduce knee instability, but may show quicker or more return to the normal compared to adults. The purpose of this study is to compare the tridimensional (3D) knee kinematics before and after ACLR in adolescents. Methods: 25 ACLD patients aged between 13 and 19 years old on a waiting list for ACLR were recruited. Bilateral knee 3D kinematic data was gathered during treadmill walking at comfortable self-selected speed using the KneeKG TM System before and 6-9 months after ACLR. Each participant underwent the same surgical protocol (2-strand hamstring tendon graft, hamstring harvest proximally and kept distally, transphyseal tibial tunnel and transepiphyseal femoral tunnel) by the same experienced surgeon. Three analyses were done: ACLD knee pre vs. post-surgery, contralateral healthy knee pre vs. post-surgery, and ACLR knee vs. healthy contralateral knee. Results: In the sagittal and transverse planes, kinematic patterns remained similar to the pre-op; maintaining the characteristic knee flexion gait pattern during single support phase which is well documented in adult ACLD (hamstring facilitation strategy). The ACLR knee exhibited a more valgus dynamic alignment compared to pre-surgery throughout the gait cycle. The healthy contralateral knee kinematics displayed no significant changes in the frontal and sagittal planes after surgery compared to the pre-op pattern. In the transverse plane, post-op gait analysis showed significantly more external rotation at heel-strike and through weight acceptance. While looking at the gait symmetry post-surgery, ACLR knee revealed significantly more valgus while remaining in greater flexion during single limb support. In the transverse plane, an external rotation tendency is observed in the ACLR knee throughout the gait cycle, except during weight acceptance. Conclusion: This study shows that kinematic adaptations found in ACLD adolescents are likely to endure short term after surgery. For example, the greater knee flexion gait pattern used before surgery is still used after ACLR. Interestingly, adolescents used an external tibial rotation adaptation to limit internal tibial instability before the surgery and this pattern was still present post-surgery. Even if theses protection strategies are efficient, the increased dynamical valgus movement seen could place the graft under pressure while increasing patellofemoral stresses, a common complaint after ACLR. Lastly, post-surgery, the contralateral knee seems to mimic the external tibial rotation gait pattern strategy seen in ACL-knee. This study demonstrates that gait protective strategies are still present short term after the surgery. Biomechanical assessment helps ID these adaptations to optimize post-op rehabilitation and prevent secondary injuries.